The Effect Of Natural Weathering Exposure And Hygrothermal Aging On The Properties Of Pultruded Hybrid Glass/Kenaf Fibre Reinforced Unsaturated Polyester Composites - Osman, Muhammad Razak (2014)
By using pultrusion technique, three types of pultruded composites at 70 V/V% fibre loading have been produced which are pultruded kenaf fibre reinforced unsaturated polyester composites (PKRC), pultruded glass fibre reinforced unsaturated polyester composites (PGRC) and pultruded glass/kenaf fibre hybrid reinforced unsaturated polyester composites (PGKRC). The objective of this study is to determine the behavior of PGKRC as compared to PKRC and PGRC after being subjected to natural weathering exposure of 200 days and six weeks of hygrothermal aging in distilled water at 65ºC. In natural weathering exposure study, PGRC specimens recorded the least absorbed moisture while PKRC specimens showed the highest. PGKRC specimens took place in between these two specimens but closer to the PGRC instead of PKRC. Similar pattern were observed in the hygrothermal aging study. Flexural and compression tests carried out on all the three types of specimen had shown a decrement in mechanical properties after a prolonged exposure. Moisture invasion is the major factor that weakened the fibre-matrix interfaces which led to mechanical properties reduction and it acts differently for different types of pultruded composites due to the nature of the constituent fibres and the arrangement of the pultruded hybrid composites. The effects of different layering pattern in PGKRC were also studied and concluded based on the resulted mechanical properties.